Risk management in student affairs : foundations for safety and success - Miller, Thomas E., 1948 November 25-; Sorochty, Roger W. (San Francisco, CA : Jossey-Bass, a Wiley brand, 2015)
'A comprehensive, accessible guide to the policies and practices of risk management in higher education. Helps practitioners understand the sources of risk in their work, and the practices and strategies they can employ to help mitigate that risk. Topics include Tort liability, contracts, state and federal violations, and resource protection'--
Framework. Differences between public and private institutions ; Personal versus institutional risk management -- The U.S. Constitution. The First Amendment ; The Second Amendment and the Fourth Amendment ; The Fifth Amendment -- Regulatory challenges. Federal and state regulations ; Discriminatory practices ; Private and voluntary organizational regulations -- Tort issues. Student activities and events, risk levels, supervision ; Hazing and student organizations ; Alcohol and drugs ; Counseling and helping services ; Providing a safe environment -- Contracts. Off-campus incidents and behavior ; Contract management ; Employment issues ; Staff development and training ; Student discipline systems -- Resource protection. Information technology: data protection ; Facilities ; Money management practices ; Physical environment: disasters and crises -- Summary. Promising practices and conclusion.
Includes bibliographical references and index.
Keywords: Student affairs services -- United States -- Administration; Universities and colleges -- United States -- Administration; Education, Higher -- United States -- Administration; Education, Higher -- Law and legislation -- United States; Schools -- Risk management -- United States; College administrators -- United States -- Handbooks, manuals, etc